سمات النثر الفني عند المعري - عيسى, حكمت; علي, فاطمة محمد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
لقد كان المعري أديباً موسوعياً غزير العطاء ، ضاع من إنتاجه الكثير ، لكن ما سلم منه يعطي فكرةً كافيةً عن أسلوبه في تأليف رسائله النثرية ، و قصائده الشعرية ، و قد سعينا في هذا البحث إلى التفصيل في السمات العامة لنثره ، و التي توصّلنا إليها نتيجة قراءتنا لأعماله المطبوعة ، التي ساعدتنا في التعرّف على الأسلوب الذي اتبعه في تدبيج رسائله وكتبه نوجزها بما يلي : المبالغة . الإيقاع . الغريب . السخرية في بعض أعماله . الاستطراد واستخدام الجمل الدعائية والاعتراضية . الحكم و الأمثال والاقتباس من الشعر والقرآن الكريم. Al-Ma’ari was an encychopedic writer with plentiful grant. Alot of his production was lost , but what was intacted of it gives an enough idea about his style in oranmenting his prose letters and his Poetic Pomes . we have sought in this research to detail in the general features of his prose which we reached as a result of reading his printed works that helped us to know his style he followed in the ornamentation of his letters and books . We summarize them as the following : The exaggeration The rhythm The strange Irony in some of his works The digression and The use of propaganda sentences and the parenthetical ones . The proverbs and wisdoms and the quotation from poetry and Koran .